2015
DOI: 10.1021/acs.langmuir.5b01663
|View full text |Cite
|
Sign up to set email alerts
|

Microstructured Films Formed on Liquid Substrates via Initiated Chemical Vapor Deposition of Cross-Linked Polymers

Abstract: We studied the formation of microstructured films at liquid surfaces via vapor phase polymerization of cross-linked polymers. The films were composed of micron-sized coral-like structures that originate at the liquid-vapor interface and extend vertically. The growth mechanism of the microstructures was determined to be simultaneous aggregation of the polymer on the liquid surface and wetting of the liquid on the growing aggregates. We demonstrated that we can increase the height of the microstructures and incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 55 publications
6
31
0
Order By: Relevance
“…For membrane separations and tissue engineering, microstructured porous crosslinked hydrogels in the form of freestanding layers resulted from iCVD onto low vapor pressure liquids. 18,19 For high molecular weight linear polymers, physical chain entanglements act as network crosslinking sites. Alternatively, hydrogel networks form by copolymerizing a hydrophilic monomer with a chemical crosslinker (Fig.…”
Section: Background For Icvd Chain-growth Polymerizationmentioning
confidence: 99%
“…For membrane separations and tissue engineering, microstructured porous crosslinked hydrogels in the form of freestanding layers resulted from iCVD onto low vapor pressure liquids. 18,19 For high molecular weight linear polymers, physical chain entanglements act as network crosslinking sites. Alternatively, hydrogel networks form by copolymerizing a hydrophilic monomer with a chemical crosslinker (Fig.…”
Section: Background For Icvd Chain-growth Polymerizationmentioning
confidence: 99%
“…Experiments carried out by the same authors, revealed that the polymeric shell’s height and roughness are inversely proportional to the liquid core’s viscosity and polymer deposition rate. By varying these parameters, CVD can be used to obtain microstructured film shells is suitable for potential applications in tissue engineering, electrolyte membranes and separations [ 24 ]. Some changes in the shells’ architecture result in increasing liquid marbles’ stability.…”
Section: Liquid Marblesmentioning
confidence: 99%
“…The contact angle is a unique characteristic of every single system, capable of imposing its own wetting regime, so that every situation corresponds to one of the above wettability measuring techniques. All the presented methods have advantages and disadvantages and can be adjusted depending on the powder [ 24 ].…”
Section: Powders’ Superficial Propertiesmentioning
confidence: 99%
“…Seidel et al, for one example, fabricated a polymer membrane with a dual-scale porosity by introducing a saturated monomer vapor in the initiated chemical vapor deposition (iCVD) process . Another example is that Bradley et al employed the same iCVD process and used a liquid substrate to fabricate micron-sized coral-like polymer films . In addition, the codeposition of monomers, cross-linkers, and small molecular porogens was also attempted by Anthamatten et al for porous polymers in the vapor deposition process. , …”
mentioning
confidence: 99%